CHARACTERISTICS OF CLASSROOM INTERACTION OF ENGLISH LANGUAGE TEACHERS IN INDONESIA AND MALAYSIA - Rido, Akhyar; Sari, Fatimah Mulya (Universitas Negeri Makassar, 2018)
This study investigates characteristics of classroom interaction of English language teachers in Indonesia and Malaysia, focusing on language accuracy and classroom discourse. A qualitative method was employed in this study while the data was gathered through observation of six teaching sessions of English language teaching in secondary schools, involving three selected Indonesian teachers and three selected Malaysian teachers. The findings reveal that all teachers performed two characteristics of classroom interaction namely language accuracy and classroom discourse. In teachers’ language accuracy, the Indonesian and Malaysian teachers delivered pronunciation, vocabulary, instructions, questions, explanations, eliciting information, use of L1, and correction of language errors. They also applied monologue, dialogue, restructure discourse, fill gaps for students lack of language, use of L1/L2 both teachers and students, accepting incomplete answers from students, and accepting one word answers. These categories improved the quality of teacher-student and student-student interaction. Therefore, the findings might be implemented more widely to enrich both Indonesian and Malaysian English language teachers.